EFEK PENYEMPROTAN PESTISIDA TERHADAP KADAR SGOT DAN SGPT PADA PETANI DI DESA SIMPANG ASAM - Nindya Nigrum Suwondo; Meri Suzana; herry Hermansyah; iis afriayani (Klinikal Sains : Jurnal Analis Kesehatan, 2023)
Pesticide is materian which used dalam increasing agricultural production. In addition includes toxic materials and dangerous. Pesticide enter into body through some way ie the digestive tract, respiratory tract and skin. Effect that caused if accumulated in long term can cause liver cirrhosis effect an increase in SGOT and SGPT in blood. Several risk factor for impaired liver function experienced by farmer use pesticide i.e age, working period, lenght of work, personal protective equipment, and position farmer against wind direction. Research purposes this is determine the analysis effect used pesticide for content SGOT and SGPT on farmers. Type of research use is associative using primary data. Sampling technique used perposive sampling and number samples use 37 samples. Correlation test in research using Chi-square. Analysis result indicate p value >0,005 there is no relationship between characteristics farmer use pesticide such as age, working periode, use of personal protective equipment, and position farmer on wind direction with content SGOT dan SGPT. Keywords : Pesticide, Liver, SGOT and SGPT